Icelandic pelagic fishing vessels_Production_Exports_CatchValues_2005-2018 - Viðarsson, Jónas R. (Zenodo, 2019)
Number of ships in Iceland, gross tonnage (GT), power (kW) and home ports. Pelagic catches by species, landing value, export value, production etc. Data used as background for development of climate adaptation plans in the ClimeFish project